PENGGUNAAN METODE SIMULATED ANNEALING DAN TRILATERATION UNTUK OPTIMASI PENEMPATAN POSISI TITIK AKSES STUDI KASUS: KANTOR KESYAHBANDARAN DAN OTORITAS PELABUHAN (KSOP) KELAS 1 TANJUNG EMAS - Arif, Muhammad; Utomo, Mardi Siswo; Yulianton, Heribertus; Utomo, Zidan Rafindra (Pixel :Jurnal Ilmiah Komputer Grafis, 2022)
Computer network technology is developing rapidly, and wired networks are being replaced by WiFi technology. The limitation of the WiFi coverage area is the main problem with this technology. Therefore, it is necessary to design for optimal placement of access points. This study analyzes the need for access point placement at KSOP Tanjung Mas Port, Semarang, where the need for internet connection via WiFi is very high. Simulation Annealing and Trilateration method is used in this study to determine the position of the access point. With the point blankspot method can be reduced.